Unique hepatic manifestations of COVID‐19‐induced immune dysregulation in children. Issue 11 (19th November 2022) - Kleinhenz, Julia; Wagner, Ellen; Afzal, Sarah Y.; Shaarbaf, Homa; De Avila, Jorge Luis; Azzam, Ruba
Abstract: The two cases we present are the first to demonstrate novel manifestations of COVID‐19 related interaction between the liver and the immune system in pediatric patients. Written informed consent was obtained from the parent/guardian to publish this report in accordance with the journal's patient consent policy.